An Adaptable Transmission Management Framework for Push-mode Hypermedia Content - Josué, Marina Ivanov Pereiraé; Moreno, Marcelo Ferreira; Costa, Romualdo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
In the delivery of hypermedia content over communication networks, the specified intermedia synchronization must be assured, despite the inherent delay and jitter of most transmission media and networks. This kind of content typically provides users multiple interaction paths, with different sets of media objects each one. In spite of that, when the hypermedia content is transmitted in push mode, users receive all media objects, regardless of the chosen interaction path. Transmission strategies that take into account the occurrence of both deterministic and non-deterministic hypermedia presentation events can decrease the waste of storage resources in the receiver side, as well as the need for network bandwidth. This work proposes a framework for an adaptable management of pushmode hypermedia content transmission. Adaptability is achieved by supporting multiple transmission strategies that may employ multiple transmission channels, which are built upon a content analysis for the identification of deterministic and non-deterministic hypermedia presentation events. Methods for instantiating the framework in the context of Ginga-NCL application transmission are also discussed over multiple transmission scenarios, in comparison with the existing, unmanaged content transmission.